Mediating Role of Aesthetic Experience between Environmentally Aesthetic and Sustainable Development in Primary School Education System - Li, Yang; Mustapha, Azwady; Ayob, Salwa (Emerging Science Journal, 2024)
Researchers in Guangxi Province, China, are doing research on primary school teachers to investigate the relationship between environmental aesthetics, aesthetic experiences, and sustainable development. To conducting an analysis of the data collected from 435 elementary school teachers who participated in a structured survey, Structural Equation Modeling (SEM) with SMART PLS software was utilized. According to the conclusions of the study, there is a large and beneficial association between environmental aesthetics, aesthetic experiences, and sustainable development. Based on the findings, it is possible that enhancing environmental aesthetics could result in an increase in the number of aesthetic experiences, which could be beneficial to educational sustainable development. The research is restricted to a narrow geographic area and relies on self-reported data, both of which may restrict its capacity to be generalized. The research demonstrates that environmental aesthetics influence the educational experiences of primary teachers, notwithstanding the constraints that have been mentioned. The knowledge of this fact may have an impact on educational practices and policies pertaining to sustainability. Doi: 10.28991/ESJ-2024-SIED1-013 Full Text: PDF